Agrobacterium tumefaciens Small Lipoprotein Atu8019 Is Involved in Selective Outer Membrane Vesicle (OMV) Docking to Bacterial Cells - Knoke, Lisa Roxanne; Abad Herrera, Sara; Götz, Katrin; Justesen, Bo Højen; Günther Pomorski, Thomas; Fritz, Christiane; Schäkermann, Sina; Bandow, Julia Elisabeth; Aktas, Meriyem (Frontiers in Microbiology, 2020)
Outer membrane vesicles (OMVs), released from Gram-negative bacteria, have been attributed to intra- and interspecies communication and pathogenicity in diverse bacteria. OMVs carry various components including genetic material, toxins, signaling molecules, or proteins. Although the molecular mechanism(s) of cargo delivery is not fully understood, recent studies showed that transfer of the OMV content to surrounding cells is mediated by selective interactions. Here, we show that the phytopathogen Agrobacterium tumefaciens, the causative agent of crown gall disease, releases OMVs, which attach to the cell surface of various Gram-negative bacteria. The OMVs contain the conserved small lipoprotein Atu8019. An atu8019-deletion mutant produced wildtype-like amounts of OMVs with a subtle but reproducible reduction in cell-attachment. Otherwise, loss of atu8019 did not alter growth, susceptibility against cations or antibiotics, attachment to plant cells, virulence, motility, or biofilm formation. In contrast, overproduction of Atu8019 in A. tumefaciens triggered cell aggregation and biofilm formation. Localization studies revealed that Atu8019 is surface exposed in Agrobacterium cells and in OMVs supporting a role in cell adhesion. Purified Atu8019 protein reconstituted into liposomes interacted with model membranes and with the surface of several Gram-negative bacteria. Collectively, our data suggest that the small lipoprotein Atu8019 is involved in OMV docking to specific bacteria.